2022
DOI: 10.1155/2022/8426384
|View full text |Cite|
|
Sign up to set email alerts
|

Expression and Clinical Significance of HER2 Gene and DNMT1 in Non-Small-Cell Lung Cancer

Abstract: Objective. To explore the expression and clinical significance of HER2 and DNMT1 in non-small-cell lung cancer. Methods. The patients with non-small-cell lung cancer treated in the First Affiliated Hospital of Jiamusi University between 2018 and 2020 were enrolled in this study. The serum DNMT1 concentration and the expression of HER2 protein in lung cancer and adjacent tissues of the two groups were analyzed. Results. The DNMT1 protein concentration was significantly correlated with gender, age, and smoking h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…43 Recently, one study has demonstrated that high expression of the DNMT1 protein in the serum may increase the risk of non-small-cell lung cancer and may play a significant role in the early stages of lung cancer. 59 In human bladder cancer, DNMT1 has been involved in tumor progression, 60,61 and researchers have shown that DNMT1 could be an important predictor for the clinicopathological stage and prognosis of bladder patients. 62 Moreover, there has been some work on DNMT1 with breast cancer.…”
Section: Dnmt1 In Multiple Solid Cancersmentioning
confidence: 99%
“…43 Recently, one study has demonstrated that high expression of the DNMT1 protein in the serum may increase the risk of non-small-cell lung cancer and may play a significant role in the early stages of lung cancer. 59 In human bladder cancer, DNMT1 has been involved in tumor progression, 60,61 and researchers have shown that DNMT1 could be an important predictor for the clinicopathological stage and prognosis of bladder patients. 62 Moreover, there has been some work on DNMT1 with breast cancer.…”
Section: Dnmt1 In Multiple Solid Cancersmentioning
confidence: 99%
“…It has been reported that HER2 induces cell proliferation and the invasion of non-small-cell lung cancer by upregulating COX-2 expression via the MEK/ERK signaling pathway. In addition, the expression of HER2 can promote the development of advanced and metastatic non-small-cell lung cancer [ 36 , 37 ]. However, advances in molecular biology and sequencing techniques have more recently identified a second mechanism concerning the major oncogenic activation of HER2 : the occurrence of activating somatic mutations that results in tumor transformation.…”
Section: Her2 Alterations and Carcinogenesismentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%